2022
DOI: 10.3389/fmed.2022.867497
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of silver nanoparticles in isoproterenol-induced myocardial infarction in rats

Abstract: BackgroundSilver nanoparticles (AgNPs) are widely used in the medical field, including cardiovascular. However, limited research has investigated the effect of AgNPs on the protection of myocardial infarction (MI).ObjectivesIsoproterenol (Iso)-induced MI and the cardiac protection offered by AgNPs were investigated in the present study. Additionally, we characterized the profile of Ag in the form of nanoparticles.MethodsTwenty-four male Wistar rats were randomly divided into four groups as follows: normal, Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Contrary to what many published articles claim, exposure to AgNPs can cause mitochondrial damage in cells, including swelling, disruption of mitochondrial membrane potentials, and apoptosis induced by the mitochondrial pathway [99]. In the case of AgNPs developed by Arozal et al [98], the formulation showed advantageous effects attributed to the green synthesized method that uses alginate. By using lactate dehydrogenase (LDH) and creatine kinase-MB (CK-MB) activities, which are markers of cardiac enzyme leakage, they could show in this study that the administration of Iso in rats was linked to myocardial injury.…”
Section: Antioxidant Effectsmentioning
confidence: 87%
See 2 more Smart Citations
“…Contrary to what many published articles claim, exposure to AgNPs can cause mitochondrial damage in cells, including swelling, disruption of mitochondrial membrane potentials, and apoptosis induced by the mitochondrial pathway [99]. In the case of AgNPs developed by Arozal et al [98], the formulation showed advantageous effects attributed to the green synthesized method that uses alginate. By using lactate dehydrogenase (LDH) and creatine kinase-MB (CK-MB) activities, which are markers of cardiac enzyme leakage, they could show in this study that the administration of Iso in rats was linked to myocardial injury.…”
Section: Antioxidant Effectsmentioning
confidence: 87%
“…When comparing the AgNO 3 and AgNP groups to the Iso group, there was a significant decrease in CK-MB activity, suggesting that silver protects against myocardial damage. While both AgNO 3 and AgNPs improved cardiac enzyme markers, only AgNPs could reverse the histological alterations in the myocardium brought on by Iso [98].…”
Section: Antioxidant Effectsmentioning
confidence: 91%
See 1 more Smart Citation
“…Several previous studies have demonstrated effects of silver on hemodynamics of the left heart. Arozal et al 28 found that silver has a cardioprotective effect against myocardial infarction through the amelioration of nuclear factor kappa B expression level induced by oxidative stress overproduction. Ramirez‐Lee et al 29 demonstrated sustained vasoconstriction and increased cardiac contractility in response to silver in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of metal nanoparticles is easy to interact with targeting agents and other molecules through hydrogen bonding, covalent bonding, and electrostatic interactions, and shows higher stability and longer half-life in terms of circulation, biodistribution, and targeting target sites [ 79 ]. Arozal et al [ 80 ] used a rat model of MI induced by isoproterenol (Iso) to evaluate the protective effect of silver nanoparticles on myocardial infarction. The results showed that silver nanoparticles could reduce the level of malondialdehyde (MDA) and the expression of nuclear factor kappa-B (NF-κB) protein in the heart tissue, thereby protecting the myocardium from MI.…”
Section: Types and Properties Of Nanoparticlesmentioning
confidence: 99%